Impaired ribosome biogenesis: mechanisms and relevance to cancer and aging - Turi, Zsofia; Lacey, Matthew; Mistrik, Martin; Moudry, Pavel (Aging, 2019)
The biosynthesis of ribosomes is a complex process that requires the coordinated action of many factors and a huge energy investment from the cell. Ribosomes are essential for protein production, and thus for cellular survival, growth and proliferation. Ribosome biogenesis is initiated in the nucleolus and includes: the synthesis and processing of ribosomal RNAs, assembly of ribosomal proteins, transport to the cytoplasm and association of ribosomal subunits. The disruption of ribosome biogenesis at various steps, with either increased or decreased expression of different ribosomal components, can promote cell cycle arrest, senescence or apoptosis. Additionally, interference with ribosomal biogenesis is often associated with cancer, aging and age-related degenerative diseases. Here, we review current knowledge on impaired ribosome biogenesis, discuss the main factors involved in stress responses under such circumstances and focus on examples with clinical relevance.
Keywords: cancer; biogeneze organel; Aging; Ribosomal Proteins; ribozomy; lidé; ribosomopathy; ribozomální proteiny; Neoplasms; p53; stárnutí; zvířata; Humans; ribosome biogenesis; nádory; Organelle Biogenesis; aging; Ribosomes; Animals